2012
DOI: 10.1007/s12012-012-9191-x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Trioxide Toxicity in H9c2 Myoblasts—Damage to Cell Organelles and Possible Amelioration with Boerhavia diffusa

Abstract: Arsenic trioxide (ATO) has been long used as a chemotherapeutic agent because of its significant anticancer property. Unfortunately, the use of ATO is limited due to its cardiotoxic effects. The present study evaluates the protective property of ethanolic extract of Boerhavia diffusa (BDE) against ATO-induced toxicity on various cell organelles in H9c2 cardiomyocytes. The effects of different concentrations of ATO (5, 7.5 and 10 μM) on cell organelles like mitochondria, endoplasmic reticulum (ER), lysosome and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Decreased ΔΨm implies membrane depolarization and can trigger mitochondrion-dependent apoptosis. Consistent with previous work [17], the present study showed that ΔΨm decreased in ATO-treated cells, as shown by the fluorescence shift from the upper left to lower right of the panel. As shown in Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Decreased ΔΨm implies membrane depolarization and can trigger mitochondrion-dependent apoptosis. Consistent with previous work [17], the present study showed that ΔΨm decreased in ATO-treated cells, as shown by the fluorescence shift from the upper left to lower right of the panel. As shown in Fig.…”
Section: Resultssupporting
confidence: 93%
“…ATO exerts a rapid noxious effect on mitochondria [17]. Decreased ΔΨm implies membrane depolarization and can trigger mitochondrion-dependent apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…There are reports on the adverse effects of ATO on cardiac tissue , adult cardiac myocytes (Raghu and Cherian, 2009) and cardiac cell line (Vineetha et al, 2013) from our group as well as from other groups (Zhou et al, 2003). Oxidative stress and associated complications like inhibition of cardiac ion channels are reported to be the main pathological mechanisms responsible for cardiotoxicity.…”
Section: Discussionmentioning
confidence: 66%
“…However, treating these rats with aqueous extract of C. olitorius leaves 15 days prior to NaAsO 2 administration protected their cardiac tissue from As-induced cardiotoxicity by maintaining the activities of the aforementioned enzymes. Ethanolic extract of Boerhavia diffusa (BDE) was also found to protect H9c2 myoblasts against ATO-induced cardiotoxicity [130]. In this study, ATO treatment at varying concentrations (5, 7.5, and 10 μM) reduced the integrity of mitochondria, initiated ER stress, disrupted cytoskeletal networks, inhibited antioxidant enzymes, and increased both ROS generation and Ca 2+ load.…”
Section: Cellular Signalingmentioning
confidence: 69%